A publicidade de alimentos funcionais: efeitos da biopolítica na conduta alimentar dos indivíduos hoje - Anjos, Ideylson da Silva Vieira dos (2013)
The present research examines the functional food advertisement and has as its general objective the purpose to investigate the enunciations of this advertisement and its effects in relation with individuals. Therefore, it starts with the hypothesis that the biomedical and biotechnological development in nutritional industry promotes, especially in the media, new speeches upon functional food and consequently persuades the individuals to some new conducts in relation with their own bodies and lives. The structure of this research is divided in three chapters: 1. The functional foods; 2. The functional food advertisement; 3. The biopolitics for the functional speech. As methodological process the first chapter is developed in these specific objectives as follows: to define functional food, and to investigate its origins and its effects nowadays in the economy and in the media using authors and institutions in the medical area like Franco Lajolo and ANVISA (Agência Nacional de Vigilância Sanitária). The second chapter is developed in the following specific objectives: to analyse the published news on functional foods by the Brazilian magazine Veja and by the newspaper Folha de São Paulo , and to investigate the tendencies of the discourses of those medias in order to promote an emergency of a pragmatic conduct of the individuals towards their own lives. The third chapter is developed in the specific objective: to analyse the publications on functional food presented in the second chapter by the biopolitical and biomedical view of Nikolas Rose. The research closes itself with the presentation of some new horizons and trends for the relationship between communication and biopolitical economy. The high relevance of this research consists in the endeavour to understand, trough the advertisement, the new field of confluence between: science, politics, economy, and life. In doing so, this dissertation is placed in the Line of Research 1 Mediatic Culture and Environment of the Postgraduate Studies in Communication and Semiotics Program